3(2X-4)=X+3

Simple and best practice solution for 3(2X-4)=X+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2X-4)=X+3 equation:


Simplifying
3(2X + -4) = X + 3

Reorder the terms:
3(-4 + 2X) = X + 3
(-4 * 3 + 2X * 3) = X + 3
(-12 + 6X) = X + 3

Reorder the terms:
-12 + 6X = 3 + X

Solving
-12 + 6X = 3 + X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-1X' to each side of the equation.
-12 + 6X + -1X = 3 + X + -1X

Combine like terms: 6X + -1X = 5X
-12 + 5X = 3 + X + -1X

Combine like terms: X + -1X = 0
-12 + 5X = 3 + 0
-12 + 5X = 3

Add '12' to each side of the equation.
-12 + 12 + 5X = 3 + 12

Combine like terms: -12 + 12 = 0
0 + 5X = 3 + 12
5X = 3 + 12

Combine like terms: 3 + 12 = 15
5X = 15

Divide each side by '5'.
X = 3

Simplifying
X = 3

See similar equations:

| 6m-10=28 | | 9x-1=63-7x | | 3k+6=14 | | (x-3)(y+5)=xy-19 | | 4n^2=-6n-1 | | y=0.2x^2+0.15x+0.8 | | 3c-1=c+a | | 2H-32=5H-7 | | 3sin^2x=cosx | | -2x-6=5x-10 | | 7y=-3x+4 | | 4//4/5 | | 57=9p+3 | | 4w+4y+8x+6x-13y+4w= | | 7-3A=19 | | -1/5r=(4)4/5 | | (x)(65-x)=1050 | | y-5.22=-3.1 | | 27x+4+8x+1+y+10=180 | | 5(4g+6)=-2(-6g-3) | | 9(y+1)-14=85 | | 6=-10-o/5 | | 4w+3x-14y+3w+11x+5y= | | -35+7x=16 | | (((13x3)-3)/? | | 5x+27=-48 | | 2a=a+14 | | r-8=5r-3r-12 | | (4+2)*4=12 | | x^2+14x=28 | | 7x-6w+5x+7y+2y+4w= | | 201=249-10 |

Equations solver categories